Differential T Cell Levels of Tumor Necrosis Factor Receptor-II in Children With Autism - Ashwood, Paul (Frontiers in Psychiatry, 2018)
Autism spectrum disorders (ASD) are characterized by impairment in social interactions, communication deficits, and restricted repetitive interests and behaviors. A role for immune dysfunction has long been implicated in ASD pathophysiology, behavioral severity and to co-morbidities. The pro-inflammatory cytokine tumour necrosis factor alpha (TNFa) has been associated with ASD in some studies but little is known about its receptors. There are two receptors for TNFalpha, with TNFRI relaying many of the signals from TNFa, especially those that are rapid, whilst TNFRII relays late long-term effects of TNF. The soluble versions of these receptors can neutralize the cytokines effects. In this study we assessed levels of TNFa and its receptors in 36 children with a confirmed diagnosis of ASD and 27 confirmed typically developing (TD) controls, 2-5 years-of-age. Children with ASD had higher levels of TNFRII on T cells compared to controls following cell stimulation. Levels of sTNFRII were decreased in cell supernatants following stimulation in ASD. Overall these data corroborate the role of inflammatory events in ASD and align with previous studies that have shown altered adaptive cellular immune function in children with ASD. Future longitudinal analyzes of cellular immune function and downstream signaling from immune receptors will help further delineate the role of inflammation in ASD.